2006
DOI: 10.1063/1.2234274
|View full text |Cite
|
Sign up to set email alerts
|

In-polar InN grown by plasma-assisted molecular beam epitaxy

Abstract: We study the effect of different deposition conditions on the properties of In-polar InN grown by plasma-assisted molecular beam epitaxy. GaN buffer layers grown in the Ga-droplet regime prior to the InN deposition significantly improved the surface morphology of InN films grown with excess In flux. Using this approach, In-polar InN films have been realized with room temperature electron mobilities as high as 2250cm2∕Vs. We correlate electron concentrations in our InN films with the unintentionally incorporate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
104
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(115 citation statements)
references
References 22 publications
(17 reference statements)
9
104
0
Order By: Relevance
“…Hydrogen has also been proposed as a source of conductivity in another novel semiconductor material InN, which is actually similar in many respects to TCOs (see Section 5). In that material, there is currently intense debate over whether hydrogen can be seen as the dominant source of conductivity, whether it is present in sufficient quantities, and whether it remains dominant over native defects over the whole Fermi level range spanned in existing material [113][114][115][116][117][118][119][120][121][122]. Such considerations may be expected to apply to TCO materials as well, and further investigations in this area are still required.…”
Section: Origin Of the Bulk N-type Conductivity?mentioning
confidence: 99%
“…Hydrogen has also been proposed as a source of conductivity in another novel semiconductor material InN, which is actually similar in many respects to TCOs (see Section 5). In that material, there is currently intense debate over whether hydrogen can be seen as the dominant source of conductivity, whether it is present in sufficient quantities, and whether it remains dominant over native defects over the whole Fermi level range spanned in existing material [113][114][115][116][117][118][119][120][121][122]. Such considerations may be expected to apply to TCO materials as well, and further investigations in this area are still required.…”
Section: Origin Of the Bulk N-type Conductivity?mentioning
confidence: 99%
“…[4][5][6] It is well known that continued InN growth decreases both the thin-film conductivity as well as the thin-film dislocation density. [1][2][3]7 Furthermore, it was shown that conductivity and dislocation densities correlate with similar power-law dependencies on the film thickness. 4,8 The density of threading dislocations scales with a power-law dependence on the InN film thickness in the range 300 nm .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] InN grown by molecular-beam epitaxy or metalorganic vapor phase deposition techniques is intrinsically n-conductive and the lowest intrinsic electron density reported so far was achieved using molecular-beam epitaxy (MBE) with approximately 10 17 cm -3 . 4 In addition to the intrinsic n-type conductivity an electron accumulation layer is formed on InN thin-film surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a strong electron accumulation occurs at the InN film surfaces 12,13 with a large sheet density in the low-to-mid 10 13 cm À2 range. [12][13][14][15][16][17] Consequently, detecting potential p-type conductivity in the InN bulk using conventional contact-based electrical measurements is not possible, since the surface inversion layer with high electron density conceals the region with free holes. 18 Up to date, only Mg has proven to successfully p-type dope InN, [18][19][20][21] and free holes in InN:Mg films have been experimentally identified by electrolyte capacitance-voltage, 18,22,23 thermopower, [23][24][25] 27 and infrared reflectometry 28 measurements.…”
Section: Introductionmentioning
confidence: 99%